A Survey on Multipath Routing Protocol for Wireless Sensor Networks Based on Infrastructure - Jin, Yongxian; Zhu, Hong (IJRDO -Journal of Computer Science Engineering, 2016)
Abstract: With the development of science and technology of the times, the wireless sensor network has been inextricably linked with people’s lives, the traditional ad hoc network has been insufficient to meet the needs of people in all aspects. Among them, the quality of the wireless sensor network routing technology plays a vital role to achieve the success of using the applications. In this paper, some infrastructure based multipath routing technologies for wireless sensor network are studied deeply, and they are divided into three categories: energy-aware multipath routing protocol, hierarchy based multipath routing protocol and ant based multipath routing protocol. The current typical multipath routing protocols are classified, analyzed and compared, and some new ideas for future research work are proposed.